Understanding the acquisition, usage, and disposal behaviours in sustainable food consumption: A framework for future studies - Thi Xuan Dieu Phan (Cleaner and Responsible Consumption, 2024)
Food sustains human life, but household food consumption impacts negatively on the environment. Therefore, many studies in the literature focus on sustainable food consumption. However, these studies are quite fragmented and study only some aspects of food consumption. By applying the thematic analysis approach to available studies in the literature, this research aims to build a framework covering all three phases of food consumption: the acquisition phase (purchasing ingredients), usage phase (cooking, eating, sharing leftover food), and disposal phase (food waste). The framework proposed in this research can become a more comprehensive reference source for future studies in sustainable food consumption topics. In specific, policymakers can use this framework to design effective campaigns/policies to promote sustainable food consumption practices of their residents. Future researchers can reference this framework to conduct more comprehensive studies on sustainable food consumption topics.